Average Error: 0.0 → 0.0
Time: 7.9s
Precision: 64
\[e^{x} - e^{4}\]
\[e^{x} - e^{4}\]
e^{x} - e^{4}
e^{x} - e^{4}
double f(double x) {
        double r8136562 = x;
        double r8136563 = exp(r8136562);
        double r8136564 = 4.0;
        double r8136565 = exp(r8136564);
        double r8136566 = r8136563 - r8136565;
        return r8136566;
}

double f(double x) {
        double r8136567 = x;
        double r8136568 = exp(r8136567);
        double r8136569 = 4.0;
        double r8136570 = exp(r8136569);
        double r8136571 = r8136568 - r8136570;
        return r8136571;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[e^{x} - e^{4}\]
  2. Final simplification0.0

    \[\leadsto e^{x} - e^{4}\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "exp(x)-exp(4)"
  (- (exp x) (exp 4.0)))